THE IMPLEMENTATION OF THE PHONICS METHOD IN IMPROVING THE READING SKILLS OF GRADE 1 STUDENTS AT SDN 4 GERESIK TASIKMALAYA - Al Humaira, Siti Aisyah; Lu`luil Maknun (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to improve students' reading skills by implementing the phonics teaching method in the first grade of SDN 4 Geresik Tasikmalaya. In this study, we used the Classroom Action Research (CAR) Method following the Kemmis and McTaggart model, which consists of two cycles. Each cycle involves the stages of planning, implementation, observation, and reflection. Data were collected through observation, interviews, pretest-posttest, and documentation. The results of the study showed that the implementation of the phonics method succeeded in improving the reading skills of grade 1 students, both in recognizing letters, spelling words, reading simple sentences, and understanding the contents of the reading. This can be seen from the increase in reading test scores and student activities during the learning process.